THE EFFECTS OF MEDICAL SUPPLY CHAIN, LEGAL CERTAINTY, AND ASPECTS OF FINANCIAL MANAGEMENT ON THE HEALTH FACILITIES: A CASE STUDY INDONESIAN NATIONAL ARMY - Sutarno, Sutarno (International Journal of Supply Chain Management, 2020)
Abstract- The purpose associated with this research is to investigate the effects of the medical supply chain, legal certainty and aspects of financial management on the healthcare facilities on the Indonesian national army. The primary data collection methods were used to collect the data from the respondents and PLS-SEM was employed for the analysis. The findings exposed that all the predictors such as the supply chain as well as legal certainty and aspects of the financial management have a positive influence on the medical healthcare facilities of the Indonesian national army. These findings give insight to the policymakers and implementers that they develop as well as implement the policies that enhance the medical supply chain, legal certainty and aspects of the financial management impact on the healthcare facilities.